Upper Limb Rehabilitation Device with Force Control Feedback using ESP32 microcontroller - Mohd Zakri, Nurul Atikah; Abdul Rahman, Hisyam (Evolution in Electrical and Electronic Engineering, 2023)
Upper limb rehabilitation device was proposed instead using old-training rehabilitation in hospital or medical hubs. Exercise therapy is an effective rehabilitation treatment, and the goal is to improve the motor coordination, and to prevent secondary complications, such as muscle atrophy and muscle spasticity. In addition, the upper limb rehabilitation training method is the therapist one-to-one manually assisted motor training in medical treatment, which is having several limitations. It uses most basic principle of motor function recovery as the medical theoretical basic of rehabilitation training. It contains two main aspect, central nervous system who have degree of plasticity of the brain injury and motor function recovery of the patient. In this paper, game-based therapy will be exposed to the patient which is having better performance and convenience ways than traditional rehabilitation. A simple video game will be created using Unity Engine software. Since stroke patients have difficulty moving their hands, the mechanical structure of this study is based on a human arm anatomy skeleton that provides physical assistance and supports stroke patient movement during therapy. The upper limb rehabilitation exoskeleton has one degree of freedom (DOF) and a range of motion (ROM) from 0º to 90º. The resistive training motion of the patient’s flexion or extension can be mimicked or followed by the force control technique. Hence, two healthy subjects are used to test the upper limb rehabilitation devices. The findings indicate that the device is safe for stroke patients to use in their rehabilitation therapy. The device has the potential to increase stroke patients’ motivation to continue their rehabilitation process. However, additional research is required.